A Heart of Myeloid: Extramedullary Chronic Myelomonocytic Leukemia-2 Presenting as a Myeloid Sarcoma of the Pericardium Causing Recurrent Pericardial Effusions - Frisch, Austin; Boyapati, Rohan; Parikh, Ruja; Menezes, Geetha; Tipirneni, Niharika; Ajebo, Germame; Shafer, Danielle (Journal of Medical Cases, 2025)
Chronic myelomonocytic leukemia (CMML) is a rare neoplasm that has a roughly 15-30% chance of transforming into acute myeloid leukemia (AML). Acute leukemias have been known to cause pleural or pericardial effusions but having CMML transform into AML while presenting as a cardiac myeloid sarcoma causing pericardial effusions makes this case unique. A 59-year-old patient presented to the emergency room with shortness of breath and was found to be in cardiac tamponade requiring urgent care. The thoracic surgery team performed a pericardiectomy and placed a window drain. Cardiac tissue biopsy proved cardiac myeloid sarcoma with immature blasts and myeloid cells. Initial bone marrow biopsy on admission showed hypercellularity with 19% blasts and abnormal monocytes with multilineage dysplasia on aspirate differential, with positive KRAS and TET2 mutations on next-generation sequencing analysis. There was no evidence of a BCR/ABL1 fusion on fluorescence in situ hybridization (FISH), and chromosomal analysis demonstrated a normal karyotype. At this time, the patient met the WHO criteria for a CMML-2 diagnosis. A follow-up bone marrow biopsy closer to discharge showed a 33% blast count pointing towards a CMML-2 transformation into AML. Remarkably, he was able to improve and was discharged from the hospital. He was admitted again to the hospital to initiate chemotherapy. Such complex cases are rarely reported. Here we discuss the diagnosis and treatment of CMML transformed into AML as well as the rarity of cardiac myeloid sarcomas with an in-depth literature review.